Occurrence and severity of cocaine-induced hallucinations: Two distinct phenotypes with shared clinical factors but specific genetic risk factors. (1st March 2022) - Zerdazi, El-Hadi; Curis, Emmanuel; Karsinti, Emily; Icick, Romain; Fortias, Maeva; Batel, Philippe; Cottencin, Olivier; Orizet, Cyrille; Gay, Aurélia; Coeuru, Philippe; Deschenau, Alice; Lack, Philippe; et al.
Abstract: Cocaine-induced transient hallucinations (CIH) are a frequent complication following cocaine intake that is associated with addiction severity. Methods: Two hundred and forty-two non-psychotic and Caucasian lifetime cocaine users were included in a French multicentric study. Clinical variables and dopamine pathway genotype data were extracted and tested with CIH scores using a zero-inflated binomial model, which allows for the exploration of factors associated with occurrence and severity separately. Results: Cocaine dependence ( p occurrence = 6.18 × 10 -5, p severity = 9.25 × 10 -8 ), number of cocaine dependence DSM IV-Tr criteria ( p occurrence = 1.22 × 10 -7, p severity = 5.09 × 10 -6 ), and frequency of intake during the worst period of misuse ( p occurrence = 8.51 × 10 -04, p severity = 0.04 ) were associated with greater occurrence and higher severity of CIH. The genetic associations did not yield significant results after correction for multiple tests. However, some nominal associations of SNPs mapped to the VMAT2, DBH, DRD1, and DRD2 genes were significant. In the multivariate model, the significant variables were the number of cocaine dependence criteria, lifetime alcohol dependence, and the nominally associated SNPs. Conclusion: Our study shows that CIH occurrence and severity are two distinct phenotypes, with shared clinical risk factors; however, they likely do not share the same genetic background. Highlights: Cocaine-induced hallucination (CIH) score distribution fits with a population mixture of resistant and vulnerable patients. CIH occurrence and CIH severity share clinical risk factors. CIH occurrence and CIH severity display different genetic risk factors. Nevertheless, some variants of the VMAT2 gene seem to be implicated in both the occurrence and severity of CIH.